The Importance Of Effective Communication In Strengthening The Relationship Between Presidents And Coaches Of Sports Clubs - zerouak nadjib (sports creativity, 2025)
(not more than 10 Lines) : Communication is an important social process, without which no individual, group or organization can live. Communication is the means by which an individual communicates his or her experiences and experiences to others. At the same time, communication is a means for others to convey their thoughts, opinions and experiences to the individual Communication is part of the normal life of the human society, preserved and deported from one generation to another. Indeed, man is always in contact with the individuals who live and work with him in society to communicate with them. It is said that any successful sports club must be based on two basic issues, namely the administrative and technical staff. When the communication between these is true and based on scientific grounds, it is effective at all levels and thus be positive relations in line with the aspirations of the members of the club as a whole,In this study, we used the descriptive method to conduct this field research. The research community in our study is the municipality of Messila clubs and we randomly selected the sample, which represents 35% of the studied statistical community